Floral and Bird Excreta Semiochemicals Attract Western Carpenter Ants - Renyard, Asim; Gries, Regine; Cooper, Stephanie L.; Gooding, Claire E.; Breen, Jenelle C.; Alamsetti, Santosh Kumar; Munoz, Ashley; Gries, Gerhard (Frontiers in Ecology and Evolution, 2022)
Ant colonies have vast and diverse nutritional needs but forager ants have limited mobility to meet these needs. Forager ants would accrue significant energy savings, if they were able to sense and orient towards odor plumes of both carbohydrate and protein food sources. Moreover, if worker ants, like other flightless insects, had reduced olfactory acuity, they would not recognize the specific odor signatures of diverse carbohydrate and protein sources, but they may be able to orient towards those odorants that are shared between (macronutrient) food sources. Using the Western carpenter ant, Camponotus modoc, as a model species, we tested the hypotheses that (1) food sources rich in carbohydrates (aphid honeydew, floral nectar) and rich in proteins (bird excreta, house mouse carrion, cow liver infested or not with fly maggots) all prompt long-distance, anemotactic attraction of worker ants, and (2) attraction of ants to plant inflorescences (fireweed, Chamaenerion angustifolium; thimbleberry, Rubus parviflorus; hardhack, Spiraea douglasii) is mediated by shared floral odorants. In moving-air Y-tube olfactometer bioassays, ants were attracted to two of four carbohydrate sources (thimbleberry, fireweed), and one of four protein sources (bird excreta). Headspace volatiles of these three attractive sources were analyzed by gas chromatography-mass spectrometry, and synthetic odor blends of thimbleberry (7 components), fireweed (23 components) and bird excreta (38 components) were prepared. In Y-tube olfactometer bioassays, synthetic blends of thimbleberry and fireweed but not of bird excreta attracted ants, indicating that only the two floral blends contained all essential attractants. A blend of components shared between thimbleberry and fireweed was not attractive to ants. Our data support the conclusion that C. modoc worker ants can sense and orient towards both carbohydrate and protein food sources. As ants were selective in their responses to carbohydrate and protein resources, it seems that they can discern between specific food odor profiles and that they have good, rather than poor, olfactory acuity.